Success of the Cracow X Archives Team – case study of Ewa C. - Iwanicka, Paulina (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The Cracow X Archives Team is a group composed of police officers of the Criminal Division and the Department of Investigation at the Police Headquarters in Cracow. It deals with the most difficult criminal cases such as unexplained murders committed many years ago, people mysteriously missing, detection of serial killers. This article presents examples of the many successes of the Cracow X Archives Team. It also presents some characteristics and methods of the officers’ work. One of the cases has been described in detail. It concerns the mysterious disappearance of Jan L., who on 17 July 2000 left home and never returned.